A change management perspective of the adoption and implementation of an across the curriculum literacy innovation - Havel, Peter Donald (Curtin University, 2001)
This thesis describes a longitudinal case study conducted in a secondary high school in the North West of Western Australia that was implementing an across the curriculum literacy strategy called Effective Reading in the Content Areas (ERICA). The study was conducted from an educational change management perspective where the adoption and implementation of ERICA was viewed against an educational change management framework. The impact of the adoption and implementation of ERICA on the teaching staff and student writing competence was investigated. The study has demonstrated that an educational change management framework is a useful tool for making the decision to adopt an innovation and for guiding the subsequent implementation. In addition, the study has highlighted the need to plan appropriately using tried and effective planning cycles and to recognize that the outcomes of any implementation of an innovation are unpredictable because of the complex interaction of change principles. Furthermore, the study has highlighted the complexity of the task of trying to improve student writing competence. Much effort was expended with little resultant improvement in student writing competence. This outcome can be rationalized, but considerable change is required in the way in which a traditional school operates before significant improvements in student writing competence will be seen.